Analysis on the Economic Recovery in the Post-COVID-19 Era: Evidence From China - Jiang, Dayang; Wang, Xinyu; Zhao, Rui (Frontiers in Public Health, 2022)
As a major public health emergency, the COVID-19 pandemic has had a huge impact on economies all over the world. The experience of post-COVID-19 economic recovery is of great significance for achieving sustainable and high-quality economic development. Taking the economic development of China as an example, based on the theory of resilient economy and related measurement methods, this article selects five major indicators that are generally recognized as closely connected with economic resilience to construct a system of economic resilience indicators. In addition, the autoregressive integrated moving average (ARIMA) model is used to predict gross domestic product (GDP) under the scenario of no epidemic. The actual value of China's GDP is compared with the predicted value in the absence of the epidemic, verifying that strong economic resilience plays an important role in the country's economic response to major shocks. Based on the results, policy recommendations are made for countries to strengthen their economic resilience in the postepidemic era.